Identification of amniotic fluid metabolomic and placental transcriptomic changes associated with abnormal development of cloned pig fetuses. Issue 3 (17th January 2019) - Ao, Zheng; Li, Zicong; Wang, Xingwang; Zhao, Chengfa; Gan, Yanmin; Wu, Xiao; Zeng, Fang; Shi, Junsong; Gu, Ting; Hong, Linjun; Zheng, Enqin; Liu, Dewu; et al.
Abstract: Piglets cloned by somatic cell nuclear transfer (SCNT) show a high incidence of malformations and a high death rate during the perinatal period. To investigate the underlying mechanisms for abnormal development of cloned pig fetuses, we compared body weight, amniotic fluid (AF) metabolome, and placental transcriptome between SCNT‐ and artificial insemination (AI)‐derived pig fetuses. Results showed that the body weight of SCNT pig fetuses was significantly lower than that of AI pig fetuses. The identified differential metabolites between the two groups of AF were mainly involved in bile acids and steroid hormones. The levels of all detected bile acids in SCNT AF were significantly higher than those in AI AF. The increase in the AF bile acid levels in SCNT fetuses was linked with the downregulation of placental bile acid transporter expression and the abnormal development of placental folds (PFs), both of which negatively affected the transfer of bile acids from AF across the placenta into the mother's circulation. Alteration in the AF steroid hormone levels in cloned fetuses was associated with decreased expression of enzymes responsible for steroid hormone biosynthesis in the placenta. In conclusion, cloned pig fetuses undergo abnormal intrauterine development associated with alteration of bile acid and steroid hormone levels in AF, which may be due to the poor development of PFs and the erroneous expression of bile acid transporters and enzymes responsible for steroid hormone biosynthesis in the placentas. Abstract : Amniotic fluid (AF) metabolomics and placental transcriptomics analysis revealed the cloned pig fetuses undergo abnormal intrauterine development associated with alteration in AF metabolites mainly involving bile acids and steroid hormones. The changes in the levels of bile acids and steroid hormones in the AF of cloned pig fetuses may be due to the poor development of placental folds and the erroneous expression of bile acid transporters and enzymes responsible for steroid hormone biosynthesis in the placentas. This study provides useful information to understand the mechanism underlying the abnormal development of cloned pig fetuses.